2016
DOI: 10.1016/j.gene.2016.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-inducing and anti-proliferative activities of isoliquiritigenin and all-trans-retinoic acid on B16F0 melanoma cells: Mechanisms profiling by RNA-seq

Abstract: Melanoma is a cancer that arises from melanocytes, specialized pigmented cells that are found predominantly in the skin. The incidence of malignant melanoma has significantly increased over the last decade. With the development of therapy, the survival rate of some kind of cancer has been improved greatly. But the treatment of melanoma remains unsatisfactory. Much of melanoma's resistance to traditional chemotherapy is believed to arise intrinsically, by virtue of potent growth and cell survival-promoting gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…In our previous studies, we demonstrated that differentiation of mouse melanoma cells induced by ISL was responsible for diminishing cancer cell cachexia [26]. We also found that ISL altered melanin anabolism and glycolysis of mouse melanoma cells in our recent work [27, 28]. In this study, we hypothesized that ISL was capable of inducing human melanoma reprogramming and we investigated the underlying mechanism of action.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our previous studies, we demonstrated that differentiation of mouse melanoma cells induced by ISL was responsible for diminishing cancer cell cachexia [26]. We also found that ISL altered melanin anabolism and glycolysis of mouse melanoma cells in our recent work [27, 28]. In this study, we hypothesized that ISL was capable of inducing human melanoma reprogramming and we investigated the underlying mechanism of action.…”
Section: Discussionmentioning
confidence: 91%
“…ISL has been shown to have anti-tumor activity in vitro and in vivo [2224]. Previously, we reported that ISL induced cancer cell differentiation [25, 26], and reduced glycolysis in a mouse melanoma cell line [27, 28]. Despite these advances, very little is known about the pharmacological mechanism of action of ISL in human melanoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have indicated that ROS are second messengers that activate the MAPK cascade and the NF‐κB transcription factor, and it has been suggested that ROS‐induced apoptosis is mediated via the MAPK and NF‐κB pathways (Akanda et al, ; Liu et al, ; Panahi, Pasalar, Zare, Rizzuto, & Meshkani, ). A recent study indicated that ISL induces apoptosis by inhibiting NF‐κB in chondrocyte‐like ATDC5 cells, and can also exert its antiproliferative effects by regulating ROS levels and MAPK signaling in B16F0 melanoma cells (Chen et al, ; Ji et al, ). In line with these findings, the results of our study revealed that ISL increases the expression levels of p‐JNK, p‐p38, and IκB, while decreasing the levels of p‐ERK, p‐STAT3, NF‐κB (p65) in cytoplasm and STAT3, NF‐κB (p65), and p‐IκB in nucleus (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of RNA sequencing (RNA-seq) technology has expanded the diagnostic, prognostic and therapeutic opportunities in cancer research, allowing the recognition of gene fusions and differential expression of disease-associated transcripts 17, 18 . In the melanoma field, many studies have focused on RNA-seq of melanocytes 19 and melanoma cell lines 2022 and only very recently few of them on whole tumor samples or single malignant, immune, stromal and endothelial cells 18, 2326 . In veterinary medicine, this technique has been used in recent years to study degenerative diseases and stress-related conditions and only rarely has it applied to tumor analysis in canine head and neck carcinoma, mammary carcinoma and lymphoma 2730 .…”
Section: Introductionmentioning
confidence: 99%